Evolution of customer communication managementover the decades - Renuka Kulkarni (North American Journal of Engineering Research, 2024)
Customer communication management (CCM) software tools are designed to create and deliver personalized, multichannel communications. It provides business organizations with secure, cost-effective, efficient, and reliable solutions for managing customer communications. CCM tools fit into customer engagement needs in various domains such as insurance, banking, utility, and healthcare. In this article, we will look at how customer communication management had evolved from its early days whenthe industry was focused on just the composition and management of documents to providing the best-personalized customerexperience for today's techno-savvy customers